Conscience Working within Prudentia. Instructed by Thomas Deman's Reading of Aquinas - Ryan, F?inche (My University, 2022)
The French Dominican Thomas Deman (1899–1954) argued for the restoration of the virtue of prudentia against a background of moral theology and philosophy that, as he saw it, had replaced the centrality of prudenti a with a centrality of conscience. This article will follow Deman in his reading of Aquinas and develop an understanding of prudentia as a moral virtue of the intellect, which co-ordinates the good life, the moral life. Conscience is a moment within the performance of prudentia. The argument of the paper is that, while conscience and prudentia are both important for good human decision-making, they should not be seen as rival concepts but rather, conscience should be understood as working within the virtue of prudentia. Specifically, the argument is that the role of conscience passes into the practical order only when it is enacted via the virtue of prudentia.
PUBLISHED
Keywords: Theology, Prudentia, decision-making, conscience; Thomas Deman op; Thomas Aquinas; Virtue; Identities in Transformation; Theology; Theology of Thomas Aquinas; Advocacy and political participation; Community; Education; Legislation; Relationships; Social participation